Phytophthora rot - a new disease of vanilla (Vanilla planifolia Andrews) in India - Thomas, R Suseela Bhai, Joseph (Journal of Spices and Aromatic Crops, 2000)
A severe rot disease affecting beans, leaves and stems of Vanilla planifolia was observed during the South West monsoon season at Koothattukulam and surrounding areas (Emakulam District, Kerala, India). The causal organism was identified as Phytophthora meadii and its pathogenicity was proved. This is the first report of Phytophthora disease of vanilla in India.